Pemanfaatan Teknologi Informasi Digital dalam Pengembangan Pendidikan Madrasah dan Pesantren - Syahla Icha Meta Amelia; Ahmad Irfan Mufid (IAIN Parepare, 2025)
This study analyzes the role and utilization of digital information technology in improving learning quality and educational management, focusing on integration strategies that preserve the identity of Islamic education. Using a descriptive qualitative method through literature review, the study identifies digital technology practices, implementation challenges, and strategic solutions. Findings indicate that e-learning, digital administration, and interactive platforms enhance efficiency, accessibility, and student engagement. Key challenges include limited infrastructure, low digital literacy among teachers and students, and cultural resistance. The study emphasizes a holistic approach combining infrastructure development, ongoing teacher training, and adaptive digital curriculum design, enabling madrasahs and pesantrens to equip students with digital skills while maintaining Islamic educational values